Hepatic Differentiation of Murine Disease-Specific Induced Pluripotent Stem Cells Allows Disease Modelling In Vitro - Reto Eggenschwiler; Komal Loya; Malte Sgodda; Francoise André; Tobias Cantz (Stem Cells International)
Direct reprogramming of somatic cells into pluripotent cells by retrovirus-mediated expression of OCT4, SOX2, KLF4, and C-MYC is a promising approach to derive disease-specific induced pluripotent stem cells (iPSCs). In this study, we focused on three murine models for metabolic liver disorders: the copper storage disorder Wilson's disease (toxic-milk mice), tyrosinemia type 1 (fumarylacetoacetate-hydrolase deficiency, FAH−/− mice), and alpha1-antitrypsin deficiency (PiZ mice). Colonies of iPSCs emerged 2-3 weeks after transduction of fibroblasts, prepared from each mouse strain, and were maintained as individual iPSC lines. RT-PCR and immunofluorescence analyses demonstrated the expression of endogenous pluripotency markers. Hepatic precursor cells could be derived from these disease-specific iPSCs applying an in vitro differentiation protocol and could be visualized after transduction of a lentiviral albumin-GFP reporter construct. Functional characterization of these cells allowed the recapitulation of the disease phenotype for further studies of underlying molecular mechanisms of the respective disease.